A retrospective analysis of moderate and severe COVID-19 pneumonia with special reference to the use of Adjuvant Tocilizumab - Pratik Raval; Benny Jose Panakkal; Dinesh Joshi; Karthik Natrajan; Anand Shukla; Gajendra Dubey; Sibasis Sahoo; Subhendu Bajpai (Archives of Medicine and Health Sciences, 2022)
Background and Aim: Coronavirus disease 2019 (COVID-19) pneumonia is associated with a hyper-inflammatory syndrome which may cause life-threatening acute respiratory distress syndrome. The aim of this study was to evaluate the safety and efficacy of an anti-inflammatory agent, tocilizumab (TCZ), a monoclonal antibody that targets the interleukin 6 receptor. Materials and Methods: We included 53 patients admitted between April and July 2020 with COVID-19 pneumonia who received TCZ. Patients received one intravenous infusion of TCZ, dosed at 8 mg/kg, up to a maximum dose of 800 mg. All patients were evaluated with clinical, laboratory, and radiological parameters. Results: Out of 53 patients 28 (52.8%) had severe disease and 25 (47.2%) had the moderate disease. The mean age was 55 years. The most common presenting symptom was fever (73%; n = 39). C-reactive protein (CRP), neutrophil-lymphocyte ratio (NLR), d-dimer, and ferritin levels were elevated at baseline. After TCZ administration CRP, ferritin and NLR levels reduced significantly whereas d-dimer levels did not fall. Pulmonary fibrosis may be observed later in the course of the disease. All the mortality occurred in patients who had severe disease on presentation. There was no difference in outcomes according to gender, diabetic status, and presence of preexisting cardiac disease. Conclusion: Overall, TCZ administration is safe and effective in improving clinical and laboratory parameters with a possible reduction in the need for ventilatory care and duration of intensive care unit stay, particularly in patients with moderate severe acute respiratory syndrome coronavirus- 2 disease. However, our results should be considered preliminary and should be interpreted with caution as they stem from an uncontrolled series.